AGENDA SETTING IN GENERAL ELECTION BROADCASTS DURING THE CAMPAIGN PERIOD ON METRO TV AND TV ONE - Shabana, Amin; Sinaga, Astriana Baiti; Kasim, Azahar (Universitas Muhammadiyah Jakarta, 2024)
This study aims to examine the agenda-setting of election broadcast content on Metro TV and TV One during November 28, 2023, to February 10, 2024. It also seeks to identify differences in election coverage between the two television stations. Using a qualitative approach, the study analyzes election news aired during the campaign stage, focusing on variations in the political narratives presented. The findings reveal distinct agenda-setting and framing approaches between the two outlets. Metro TV frequently highlights the Anies Baswedan ticket, often portraying it positively compared to the other two presidential and vice-presidential candidates. In contrast, TV One adopts a more neutral stance, offering coverage that avoids overt bias while addressing violations related to the 2024 election. These findings contribute to the development of agenda-setting theory and have practical implications for both media and political discourse.